Continuous Embezzlement in Office According to the Criminal Code - Paruhum, Raja Toga; Hafidz, Jawade (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The law also plays a role in protecting individual rights, ensuring that everyone gets equal and fair treatment in the eyes of the law. Therefore, the law is very important in building a stable and just social order. That every person in the territory of Indonesia is obliged to comply with the laws and regulations in force in Indonesia and no one can be immune from the law, and all actions must be based on and have consequences in accordance with the laws and regulations in the Unitary State of the Republic of Indonesia, which aims to realize an orderly, prosperous and just life in society, nation and state in order to achieve the goals of the state as mandated in the opening of the 1945 Constitution of the Republic of Indonesia. This criminal law is included in public law which regulates the relationship between the state and individuals and the public interest, in contrast to private law which regulates the relationship between individuals and personal interests. Acts that are prohibited by criminal law and are subject to punishment are known as criminal acts or offenses. In the Criminal Code (KUHP), criminal acts are classified into two types, namely crimes and violations. Examples of crimes include theft, embezzlement, assault, and murder, while examples of violations include delinquency, begging, and vagrancy. Talking about professions, of course, one of them is bound to an organization or agency that is certainly inseparable from the element of trust. Someone who has received trust in an agency certainly has a position or title when the element of trust has been carried out, of course someone is obliged to maintain it. The crime of embezzlement which is a crime often occurs in various fields and even the perpetrators are in various levels of society. Both the lower and upper classes commit this crime. Seeing the many cases of embezzlement that occur in Indonesia, of course this is very concerning. Abuse of Trust dominates as an element of this crime of embezzlement. The crime of embezzlement is regulated in the Criminal Code (hereinafter abbreviated as the Criminal Code) Article 372 (ordinary embezzlement), Article 373 (minor embezzlement), Article 374 and Article 375 (aggravated embezzlement) and Article 376 (embezzlement within the family).